KOMUNIKASI TERAPEUTIK MELALUI PRAKTIK YOGA HEALING DI WISUDA YOGA KABUPATEN KLUNGKUNG - -, Putu Ayu Sri Kumala Dewi; I Dewa Ayu Hendrawathy Putri; I Nyoman Alit Putrawan (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Health maintenance is the most important factor in human life, for health is life itself. There are numerous methods practiced to maintain health, both physical, psychological, and spiritual, one of which is in the form of yoga healing the practice of yoga healing cannot be separated from the success of a communication process. Such therapeutic communication process is carried out in Wisuda Yoga Therapist Ashram in Klungkung Regency. Wisuda Yoga has their own training module on yoga healing as well as communication strategy with the clients which enables the healing process to work on not just the clients’ physical body but also, psychological, spiritual, and social aspects. The present study is urgent to be conducted due to the swift changes within the society. Said changes are sometimes are not readily accepted by the members of society and this caused shockwaves which reverberated to all aspect of life. This healing practice considered to provide an alternative in dealing with the intended shock.